Indicador de calidad: correlación de biopsia intraoperatoria y biopsia definitiva en patología mamaria y ganglio centinela año 2005 - Moyano S., Leonor; Carreño T., Laura; Sepúlveda P., Sergio; Villanueva I., María; Gutiérrez C., Lorena; Corco R. , Carla; Novoa E., Sebastián (Revista Hospital Clínico Universidad de Chile, 2007)
The frozen section is important in breast diagnosis. We compare the results between frozen section and definitive diagnosis attending to biological conduct, margins and centinel lymph node in 127 cases performed during a year. 94 cases were for diagnostic purpose, The 34 positive cases were confirmed. In 60 negative cases, one had a microscopic focus of ductal carcinoma in situ. The margins were corrected in 54/55, one showed carcinoma in less than 2mm from the border. 30 cases of centinel lymph node we studied, 4 were positive and 26 negative. There were no false positive cases. We found 2 cases with metastasis of 2 and 5 mm. in the definitive biopsy. The sensitivity, specificity, positive and negative predictive value in diagnosis was 94%, 100%, 100%, 96% respectively and in centinel lymph node was 66%, 100%,100% y 92%.